Pengaruh Toksisitas Subkronik Ekstrak Etanol Rimpang Pacing (Costus speciosus) terhadap Fungsi Hati pada Tikus - Aulia Nurfazri Istiqomah; Siti Kholisatun Nisa; Kharina Septi Lestari (Indonesian Journal of Herbal Science and Innovation, 2025)
Traditional medicine has been an integral part of healing practices for thousands of years. With its rich biodiversity, Indonesia boasts approximately 30,000 plant species with potential medicinal properties, one of which is the rhizome of Costus speciosus (pacing). This plant is known for its various benefits, including antifungal, antioxidant, anthelmintic properties, and traditional contraceptive use. The aim of this study was to investigate the subchronic toxicity of ethanol extract from pacing rhizomes on liver function in male and female rats. The experiment was conducted using Wistar rats, with two groups (10 males and 10 females per group), which were treated with a 300 mg/kg body weight dose of the extract for 90 days. Liver histology, organ index, and levels of the enzymes SGOT and SGPT were observed. The results indicated that the ethanol extract of pacing rhizomes, at this dose, did not cause significant changes in body weight, liver organ index, or SGOT/SGPT levels in both male and female rats. In conclusion, the study suggests that the ethanol extract of pacing rhizomes at 300 mg/kg body weight for 90 days does not show signs of liver toxicity in rats. These findings support the potential use of pacing rhizomes as a safe ingredient in traditional medicine. However, further studies are needed to assess possible toxic effects and animal mortality over longer durations.